The Power of The Computer-Generated Imagery (CGI) in Avengers Endgame Movie: Hyperreality Perspective - Lestari Budianto; Slamet Setiawan; Pratiwi Retnaningdyah; Pijar Krupskaya Barus; Bilqis Aurell Widya Ningsih; Diah Riska Amelia (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
In this modern era, technology plays a very important role in human life. Related to film production, Technology can emerge hyperreality -fiction reality that looks real- to provide a better experience and sensation for the viewers. Avengers Endgame movie is one of action movie that uses hyperreality for the effect. This movie is directed by Antony and Joe Ruso. This paper explores the effects of hyperreality that occurs in the superhero team. Bearing with the objective of the study, the researcher uses the theory of hyperreality proposed by Jean Baudrillard. In this paper, the researcher used a descriptive qualitative method to explore and explain how hyperreality affected the superhero team in Avengers Endgame. The result shows that CGI technology plays a very important role in creating hyperreality effects. Superheroes with incredible abilities, places, planets, weapons, and scenes are supported by CGI to enable imagination as an illusion that looks so real in the movie. Many things that do not exist and seem impossible in the real world look so real that it is difficult to distinguish between illusion and reality. That is how hyperreality effects on the Avenger Endgame movie applied.